Bernanos on the Adventure of Christian Living - Murphy, Joseph (Irish theological quarterly, 2004)
For Georges Bernanos, the call to holiness means living the spiritual adventure, the only true adventure, in a world adversely affected by sin but already redeeemed by Christ. To embark upon this adventure, the Christian must recover the evangelical values characteristic of childhood, join Christ in the agony of Gethsemani, and share in the mysterious exchange of spiritual gifts that takes place in the Church, the Communion of Saints.